Programa educativo aprendiendo en movimiento y su importancia en el proceso enseñanza aprendizaje de la cultura física en los estudiantes de 8°-9° y 10° años de la unidad educativa Alejandro Dávalos calle en el periodo 2014-2015 - Trujillo Tello, Klever Augusto (2015)
The present work research had with purpose to announce the importance of moving learning educational program in the teaching-learning process of physical culture in students of 8th, 9th and 10th year of the Educational Unit Alejandro Dávalos Calle. The disregard by teachers about the contents of the program has led to a deficient motor development in children, in addition a little physical activity and therefore high margin of sedentary….